THE TRANSFORMATION OF WOMEN'S ROLES IN PARLIAMENT: BETWEEN EMANCIPATION AND UPHOLDING HUMAN RIGHTS (CASE STUDY IN BANYUWANGI REGENCY) - Eka Lestari; Nikmatul Keumala Nofa Yuwono; Etis Cahyaning Putri (CV. RADJA PUBLIKA, 2025)
This study explores the transformation of women's roles in Indonesia's parliamentary institutions, focusing on the intersection between women's emancipation and human rights enforcement at the local level, with Banyuwangi Regency as a case study. The research analyzes how gender equality principles—enshrined in international conventions such as CEDAW and Indonesia's national legislation—are reflected in the political representation and policy contributions of female members of the Banyuwangi Regional People's Representative Council (DPRD). Employing a qualitative descriptive approach, data were collected through document analysis, interviews with female legislators and human rights activists, and secondary data from the General Election Commission (KPU) and the National Commission on Violence Against Women (Komnas Perempuan). The findings indicate that while women's representation in Banyuwangi DPRD has increased following the national 30% gender quota policy, substantive advocacy for women's rights and gender equality remains constrained by patriarchal norms, limited political resources, and institutional barriers. The study concludes that gender transformation in local parliaments like Banyuwangi is ongoing, reflecting both progress and persistent inequality in realizing women's political emancipation and human rights protection.